Project technologies in teacher-philologist training (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article the value of project technologies in teacher-philologist training is proved. Their aim, essence and content, typological characteristics are identified. The criteria of evaluation of students project activities and stages of project technology implementation within system approach from the first to the last study year are offered. The paper is focused on the advantages of project activities for higher education institutions on the whole and future teachers-philologists in particular.
Keywords: project; project technologies; project activities; teacher-philologist; system approach